Perkembangan Konservatisme di Türkiye: Pengajaran Buat Kelestarian Islam di Malaysia: The Development of Conservatism in Türkiye: Lessons for Islamic Sustainability in Malaysia - Ibrahim, Muhammad Khalis; Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2022)
Conservatism is a political philosophy that tends to preserve traditions and reject drastic change. Türkiye has a long experience of political conservatism due to the Kemalists’ radical secularization. The Justice and Development Party (Adalet ve Kalkınma Partisi-AK PARTİ) is an entity that recently champions political conservatism in Türkiye. Despite having many differences, Türkiye and Malaysia share similarities as progressive, modern, and democratic Muslim countries. This paper aims to discuss AK PARTİ’s political conservatism and analyze to what extent it can be made as an example for the sustainability of Islam in Malaysia. To fulfill this objective, primary and secondary sources related to AK PARTİ’s conservatism discourse have been referred to be used as the basis of analysis of lessons that can be taken for the sustainability of Islam in Malaysia. The comparative analysis method has also been used to compare the context of Türkiye and Malaysia to understand the limitations of lessons that Malaysia can learn based on the experience of conservatism in Türkiye. As a party with a conservative democratic ideology, AK PARTİ manages to uphold political conservatism within the context of modern democracy. This success results from a synthesis between the demands of conservatism and democracy. The political conservatism in Türkiye can be made as an example for Malaysia, especially in preserving Islam as the federal religion, the existence of the king institution, the Malay-Muslim identity, and the true essence of Islam as a societal-unifying force. This paper argues that in the Malaysia context, conservatism is an important political philosophy to be upheld in order to preserve the harmony and stability of the plural society.